2019
DOI: 10.1016/j.compositesa.2019.105493
|View full text |Cite
|
Sign up to set email alerts
|

Optimized manufacturing of thermoplastic biocomposites by fast induction-heated compression moulding: Influence of processing parameters on microstructure development and mechanical behaviour

Abstract: The optimization of processing tools and manufacturing procedures are key issues for the development of highperformance biocomposite materials. In this study, we investigated the manufacturing of commingled flax/ polypropylene fabrics by fast induction-heated compression moulding to produce lightweight thermoplastic biocomposites. The processing/microstructure/mechanical behaviour relationships of these biocomposites were established based on a careful characterisation of material's microstructure through SEM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Flax/thermoplastic fabric consists of twistless flax fibres and polypropylene (PP) fibres mixed in the ratio of 40/60 (v/v). The commingled fibres are then woven in a balanced 2x2 twill architecture to form fabrics with areal density of 400 g/m 2 [25]. For the thermoset composite, dry flax woven fabrics (Biotex Flax, 400 g/ m 2 ) also supplied by Composites Evolution and a two-part epoxy resin (1800 epoxy resin and 1805 aliphatic amine hardener) supplied by Resoltech Advanced Technology Resins, France were chosen.…”
Section: Manufacturing Of Composite Specimenmentioning
confidence: 99%
See 1 more Smart Citation
“…Flax/thermoplastic fabric consists of twistless flax fibres and polypropylene (PP) fibres mixed in the ratio of 40/60 (v/v). The commingled fibres are then woven in a balanced 2x2 twill architecture to form fabrics with areal density of 400 g/m 2 [25]. For the thermoset composite, dry flax woven fabrics (Biotex Flax, 400 g/ m 2 ) also supplied by Composites Evolution and a two-part epoxy resin (1800 epoxy resin and 1805 aliphatic amine hardener) supplied by Resoltech Advanced Technology Resins, France were chosen.…”
Section: Manufacturing Of Composite Specimenmentioning
confidence: 99%
“…It is known that the limited wettability of natural fibres towards apolar and viscous matrices such as PP leads to poor impregnation and the formation of micro and macropores. Ramakrishnan et al [25] calculated the porosity volume fraction from X-ray computed tomography analysis and reported that the pressure and temperature of the manufacturing process have a strong influence on the formation of pores. It has also been reported [29] that surface treatments can be successfully used to increase the interactions between natural fibres and polymer matrices, and significantly enhance the interfacial adhesion leading to better stiffness and possibly modifying impact strength properties.…”
Section: Visual Assessment Of Impact Damagementioning
confidence: 99%
“…Only convex shape components can be manufactured using this technique. Whereas in compression molding, heat and pressure are applied for specific time to manufacture different laminar composites [ 7 ]. The use of dies and molds in compression molding increases the lead time and production cost.…”
Section: Introductionmentioning
confidence: 99%
“…These products, manufactured at low cost [6] and in high volume, are particularly popular in the automotive sector to design and produce non-structural interior composite parts [7]. Currently, such preforms are made using a mix of plant fibres and thermoplastic fibres, such as poly-(propylene) (PP), which has good mechanical properties as well as a low melting temperature, which is an important parameter to prevent plant fibre damage during the processing stage [8,9]. To improve the end of life of these materials [10], it is interesting to study the coupling of flax fibres with a biobased and biodegradable polymer matrix such as poly-(lactid) (PLA) or poly-(β-hydroxybutyrate) (PHB).…”
Section: Introductionmentioning
confidence: 99%